The Mythology of The Tree in The Poetry of Taras Shevchenko - Жуковська, Галина (Київський національний університет імені Тараса Шевченка, 2026)
Background. The mythologeme of the tree occupies an important place in Taras Shevchenko's poetry, it represents moral and ethical values, beliefs, traditions, social ideas, historical memory, as well as psycho-emotional states of the lyrical subject. This image in the poet's artistic discourse functions as a polysemantic symbolic structure that integrates archetypal, folklore and individual-authorial meanings. Мethods. The study of the mythologeme of the tree in Taras Shevchenko's poetry is carried out using a complex of complementary methods, in particular mythocritical, structural-semiotic, and historical-literary. Results. The mythologeme of the tree in Taras Shevchenko's poetry primarily represents the sacred space of Ukraine as a topos of the native land, actualizing the nostalgic discourse of the lost "paradise" and the existential longing for it. Recreating an idyllic, dreamy image of a lost native world, the integral markers of which in Taras Shevchenko's poetry are happy lovers or a harmonious family (family), a white cottage in a blooming garden, the poet organically continues the biblical and baroque Ukrainian tradition, in which the garden is interpreted as a symbol of heavenly and earthly paradise, the center of cosmic harmony, the personification of the spiritual ideal associated with a person's stay in a state of primordial paradise idyll. The images of trees, which accumulate deep mythological symbolism, in Shevchenko's poetic concept express the inner states of the lyrical subject, his existential experience. The images of poplar, willow, viburnum, oak, etc. become tools for the psychologization of the poetic world and at the same time carriers of a broader ontological content. The indicated mythologeme functions as a symbolic-historiosophical model, which combines the motifs of the cyclical nature of being, national memory, decline and revival. At the same time, the mythologeme evolves into a universal model of the "tree of life", the archetype of the World Tree, which symbolizes the life-creating energy and the semantic completeness of being. In the poetic world of Taras Shevchenko, the mythologeme of the tree is realized as a polysemantic image-symbol, reflecting individual existential experience, folk worldview and historical memory. Conclusion. The mythologeme of the tree in Taras Shevchenko's poetry is one of the important system-forming components of the artistic and mythological picture of the world, multi-valued and archetypal, which gravitates towards the model of the World Tree and integrates the natural, socio-historical and spiritual-value dimensions of being.

Вступ. Міфологема дерева посідає важливе місце в поезії Тараса Шевченка, вона репрезентує морально-етичні цінності, вірування, традиції, соціальні уявлення, історичну пам'ять, а також психоемоційні стани ліричного суб'єкта. Цей образ у художньому дискурсі поета функціонує як полісемантична символічна структура, що інтегрує архетипні, фольклорні та індивідуально-авторські значення. Методи. Дослідження міфологеми дерева в поезії Тараса Шевченка здійснюється із застосуванням комплексу взаємодоповнювальних методів, зокрема міфокритичного, структурно-семіотичного та історико-літературного. Результати. Міфологема дерева в поезії Тараса Шевченка насамперед репрезентує сакральний простір України як топос рідного краю, актуалізуючи ностальгійний дискурс утраченого "раю" та екзистенційної туги за ним. Відтворюючи ідилічний, вимріяний образ утраченого рідного світу, невід'ємними маркерами якого в поезії Тараса Шевченка постають щасливі закохані чи гармонійна сім'я (родина), біленька хатка в квітучому садку, поет органічно продовжує біблійну й барокову українську традицію, у якій сад осмислюється як символ раю небесного і земного, центр космічної гармонії, уособлення духовного ідеалу, пов'язаного з перебуванням людини в стані первісної райської ідилії. Образи дерев, які акумулюють глибоку міфологічну символіку, в Шевченковій поетичній концепції увиразнюють внутрішні стани ліричного суб'єкта, його екзистенційний досвід. Образи тополі, верби, калини, дуба тощо стають інструментами психологізації поетичного світу й водночас носіями ширшого онтологічного змісту. Означена міфологема функціонує як символічно-історіософська модель, у якій поєднуються мотиви циклічності буття, національної пам'яті, занепаду й відродження. Водночас міфологема еволюціонує до універсальної моделі "дерева життя", архетипу Світового дерева, що символізує життєтворчу енергію та смислову повноту буття. У поетичному світі Тараса Шевченка міфологема дерева реалізується як полісемантичний образ-символ, що відображає індивідуальний екзистенційний досвід, народний світогляд й історичну пам'ять. Висновки. Міфологема дерева в поезії Тараса Шевченка є одним із важливих системотвірних складників художньо-міфологічної картини світу, багатозначний і архетипний, що тяжіє до моделі Світового дерева та інтегрує природний, соціально-історичний і духовно-ціннісний виміри буття.
Міфологема дерева в поезії Тараса Шевченка
Keywords: Ukrainian literature; myhologeme; image-symbol; archetype; mythopoetics; poetic semantics; українська література; міфологема; образ-символ; архетип; міфопоетика; поетична семантика